Sistem Pendukung Keputusan Penilaian Kinerja Karyawan Rumah Sakit Menggunakan Metode Analytical Hierarchy Process (AHP) - Rachmad Mustaqim; Siswanto Siswanto; Indra Kanedi (Jurnal Media Infotama, 2024)
The performance appraisal system currently running at Ummi Bengkulu Hospital still experiences weaknesses, including the employee appraisal process is still carried out manually and the data processing process does not use application programs in making decisions but still uses Microsoft Excel in data processing so it takes a long time. long enough. Therefore, a decision support system was designed for assessing employee performance at Ummi Bengkulu Hospital using the Analytical Hierarchy Process (AHP) method. This decision support system is designed using the PHP programming language and MySQL database. The system created can make it easy for Ummi Bengkulu Hospital to assess employee performance at Ummi Bengkulu Hospital quickly and accurately